2015
DOI: 10.1136/bmj.h2652
|View full text |Cite
|
Sign up to set email alerts
|

Challenging behaviour and learning disabilities: summary of NICE guidance

Abstract: This is one of a series of BMJ summaries of new guidelines based on the best available evidence; they highlight important recommendations for clinical practice, especially where uncertainty or controversy exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Challenging behaviors in learners with Developmental disabilities such as ASD include aggression, self-injury, stereotypic behavior, and withdrawal. It results out of interaction between personal and environmental factors (Pilling, et al, 2015). Prevalence of challenging behaviors increases with age during childhood; it reaches a peak during adolescence and young adulthood but eventually declines at late adulthood (Rattaz et al, 2018).…”
Section: Common Challenging Behaviorsmentioning
confidence: 99%
“…Challenging behaviors in learners with Developmental disabilities such as ASD include aggression, self-injury, stereotypic behavior, and withdrawal. It results out of interaction between personal and environmental factors (Pilling, et al, 2015). Prevalence of challenging behaviors increases with age during childhood; it reaches a peak during adolescence and young adulthood but eventually declines at late adulthood (Rattaz et al, 2018).…”
Section: Common Challenging Behaviorsmentioning
confidence: 99%
“…Frequently, the referred child or young person has not had a detailed or completed behavioural assessment or treatment plan, which is a widely recommended intervention . When available, it has often not been enacted, mainly because implementation is challenging as most schools, parents and carers do not have easy access to professionals with both the time and skills to assist.…”
Section: Clinical Perspectivementioning
confidence: 99%
“…Smith et al (1996) reported behavioural disorders in about 64% of their population-based cohort of adults with ID. These rates are higher in people with more severe disabilities and within inpatient settings (Pilling et al, 2015).…”
Section: Introductionmentioning
confidence: 99%